Effect of Supplementation of Multi Enzymes on Production Performance and Egg Quality Traits in White Leghorn Layers - Pandian, C.; Sundaresan, A.; Omprakash, A.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The present study was conducted to assess the effect of supplementation of Multi-enzymes with  lysophospholipids on production performance of pure line White Leghorn layers. Body weights  before and after the experiment did not differ significantly across the experimental diets. Irrespective  of the dietary treatments, the birds gained 3.83 per cent of live weight relative to its initial body  weight. Mean per cent Hen housed egg production was significantly (P
Keywords: Multi-enzymes Complex; Supplementation; Production Performance; egg quality traits; White Leghorn